Catalyst with high catalytic activity and preparation method thereof

By reacting zirconium salt WS2 and tungsten disulfide WS2 with organic ligand in an autoclave, the composite catalyst WS2-UiO-66 was solved, and the problem of limited light absorption capacity and easy recombination of photogenerated electron-hole pairs during photocatalysis was solved, achieving efficient photocatalytic degradation effect and long-life catalytic performance.

CN119608249APending Publication Date: 2025-03-14HUAIYIN INSTITUTE OF TECHNOLOGY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411632261.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-15
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

In the photocatalytic process, pure tungsten disulfide WS2 has problems such as limited light absorption capacity and easy recombination of photogenerated electron-hole pairs, which limits its photocatalytic efficiency and is difficult to recover and reuse.

Method used

The zirconium salt WS2 and tungsten disulfide WS2 were added to the mixed solution of the organic ligand N,N-dimethylformamide and acetic acid. After ultrasonic dissolution, the composite catalyst WS2-UiO-66 was heated and reacted in a stainless steel autoclave lined with polytetrafluoroethylene to prepare the composite catalyst WS2-UiO-66.

Benefits of technology

The three-dimensional structure constructed by the aminolated terephthalic acid and zirconium salt increases the specific surface area and porous structure of the catalyst, inhibits the recombination of photogenerated electron-hole pairs, improves the adsorption capacity and reaction efficiency, extends the service life of the catalyst, and has excellent degradation performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119608249A_ABST
    Figure CN119608249A_ABST
Patent Text Reader

Abstract

The invention discloses a catalyst with high catalytic activity and a preparation method thereof. Belongs to the technical field of materials, the high-activity composite catalyst of WS2-UiO-66 is prepared by one step through an in-situ synthesis method, and the preparation method comprises the following steps: adding zircon salt and tungsten disulfide into a mixed solution of N, N-dimethylformamide of an organic ligand 2-aminoterephthalic acid and acetic acid, uniformly stirring and mixing, performing ultrasonic dissolution, and drying to obtain the WS2-UiO-66 composite catalyst. Transferring into a stainless steel high-pressure kettle with a polytetrafluoroethylene lining for heating reaction; after the reaction kettle is cooled to the room temperature, taking out a product, performing centrifugal separation, sequentially washing the product with absolute ethyl alcohol and DMF for 3 times, and drying to obtain the catalyst WS2-UiO-66; wherein the stereo structure of UiO-66 can effectively inhibit the recombination of photo-induced electron-hole pairs, improve the transmission efficiency of electrons and improve the catalytic effect; in addition, the ligand containing amino provides more active sites for the catalytic reaction, and the reaction rate is increased. The operation is simple, the catalytic effect is excellent and efficient, and the phenol degradation efficiency is excellent by using a small amount of the catalyst.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of materials and relates to a catalyst with high catalytic activity and a preparation method thereof. Background Art

[0002] With the intensification of industrialization, energy crisis and environmental pollution have become increasingly serious, which has attracted widespread attention. In this context, the development of new energy and green and efficient energy conversion and utilization technologies have become a research hotspot for scholars from all over the world. Solar energy is a cheap and clean renewable energy source. Photocatalytic technology has come into people's attention because it can convert solar energy into directly usable chemical energy.

[0003] In the past few years, many transition metal sulfides and metal oxides have been used as semiconductor photocatalysts, including NiS, Cu2O, NiCo2O4 and WS2. Among them, tungsten disulfide WS2, as a typical transition metal sulfide, has a two-dimensional layered structure similar to graphene and has attracted much attention due to its excellent light absorption performance, good stability, low cost and environmental protection. Due to its good photogenerated electron-hole pair transport ability and unique optical properties, tungsten disulfide WS2 exhibits excellent performance under visible light and infrared radiation. However, pure tungsten disulfide WS2 has some disadvantages in the photocatalytic process, such as limited light absorption capacity and easy recombination of photogenerated electron-hole pairs. These problems limit its photocatalytic efficiency and make it difficult to recycle and reuse.

[0004] Therefore, loading tungsten disulfide WS2 onto different carriers such as activated carbon and mesoporous molecular sieves to synthesize heterogeneous catalysts is an effective way to overcome the shortcomings of homogeneous catalysis and thus form a composite photocatalytic material with better performance. Summary of the invention

[0005] In view of the above problems, the purpose of the present invention is to propose a catalyst with high catalytic activity and a preparation method thereof, so as to realize the conversion of solar energy into directly usable chemical energy, while overcoming the related problems of tungsten disulfide in the prior art and solving the problems raised in the above background technology.

[0006] The technical scheme of the present invention is: a preparation method of a catalyst with high catalytic activity described in the present invention, wherein zirconium salt WS2 and tungsten disulfide are added to a mixed solution of N,N-dimethylformamide and acetic acid as an organic ligand, stirred and mixed evenly, and then ultrasonically dissolved, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction; after the heating is completed, the autoclave is cooled to room temperature, the product is taken out and centrifuged, and washed with anhydrous ethanol and DMF for 3 times each, and then dried in a vacuum drying oven to obtain the catalyst WS2-UiO-66.

[0007] Furthermore, the zirconium salt is any one of zirconium tetrachloride ZrCl4 and zirconium nitrate Zr(NO3)4.

[0008] Furthermore, the preparation steps of the tungsten disulfide WS2 are as follows:

[0009] S1: Mix 20 mmol sodium tungstate NaWO4 and 20 mmol sodium sulfide Na2S in 50 mL distilled water and stir for 30 min to form a transparent solution;

[0010] S2: The transparent solution prepared in S1 was introduced into a stainless steel autoclave lined with polytetrafluoroethylene and heated at 220 °C for 6 h;

[0011] S3: After the autoclave is cooled naturally to room temperature, centrifuge, remove the supernatant, and wash with ethanol and deionized water several times;

[0012] S4: After drying in a vacuum drying oven at 70°C for 12 h, tungsten disulfide WS2 powder was obtained.

[0013] Furthermore, the organic ligand is 2-aminoterephthalic acid.

[0014] Furthermore, the molar ratio of the zirconium salt, tungsten disulfide WS2 and the organic ligand is 1:0.5-1.5:2.

[0015] Furthermore, the volume ratio of N,N-dimethylformamide to acetic acid is 1:0.2.

[0016] Furthermore, the stirring and mixing time is 30-40 minutes; and the ultrasonic treatment time is 2-3 hours.

[0017] Furthermore, the heating temperature of the autoclave is 110-130° C., and the heating time is 24 hours.

[0018] Furthermore, the centrifugal speed is 8000 rpm and the time is 10 min.

[0019] Furthermore, the drying temperature in the vacuum drying oven is 70-80° C., and the drying time is 10-12 hours.

[0020] The beneficial effects of the present invention are as follows: the composite catalyst prepared in one step by the solvent thermal synthesis method of the present invention has a larger specific surface area and a porous structure through the three-dimensional structure constructed by the amino terephthalic acid and the zirconium salt, which effectively inhibits the recombination of photogenerated electron-hole pairs, greatly improves the adsorption capacity, and thus improves the reaction efficiency; at the same time, the amino group on the organic ligand provides more active sites for the catalytic reaction, increases the reaction contact opportunities, and thus improves its catalytic efficiency; secondly, after being compounded with UIi-66, it has a longer service life and the characteristics of small amount and high efficiency in the photocatalytic process, and has excellent degradation performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a degradation curve diagram of phenol by the WS2-UiO-66 catalyst of the present invention;

[0022] Figure 2 The effect of the amount of the WS2-UiO-66 catalyst of the present invention on the catalytic effect;

[0023] Figure 3 It is a performance diagram of the reuse of the WS2-UiO-66 catalyst of the present invention. DETAILED DESCRIPTION

[0024] The specific technical solutions of the present invention are further described in detail below in conjunction with specific examples.

[0025] Reagents: sodium tungstate (NaWO4), sodium sulfide (Na2S), phenol, AR, 2-aminoterephthalic acid, zirconium tetrachloride (ZrCl4), AR, N,N-dimethylformamide, anhydrous ethanol, acetic acid, AR; all reagents were used directly without further treatment.

[0026] The present invention provides a catalyst with high catalytic activity and a preparation method thereof. The preparation method comprises: firstly, mixing 20 mmol of sodium tungstate NaWO4 and 20 mmol of sodium sulfide Na2S in 50 mL of distilled water, and continuously stirring for 30 minutes to form a transparent solution;

[0027] Then, the mixture was introduced into a stainless steel autoclave lined with polytetrafluoroethylene and heated at 220°C for 6 hours; after the autoclave was naturally cooled to room temperature, the prepared powder was taken out by centrifugation and washed several times with ethanol and deionized water;

[0028] Finally, the tungsten disulfide WS2 powder was obtained after drying at 75°C for 11 h in a vacuum drying oven for use.

[0029] Zirconium salt and tungsten disulfide WS2 are added to a mixed solution of 2-aminoterephthalic acid, N,N-dimethylformamide and acetic acid, stirred and mixed evenly, and then ultrasonically dissolved and transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating reaction; after the heating is completed, the autoclave is cooled to room temperature, the product is taken out and centrifuged, and washed with anhydrous ethanol and N,N-dimethylformamide for 3 times each, and then dried in a vacuum drying oven to obtain the catalyst WS2-UiO-66.

[0030] Example 1

[0031] 2.0 mmol of 2-aminoterephthalic acid was weighed and dissolved in 50 mL of a mixed solution of N, N-dimethylformamide and acetic acid in a volume ratio of 1:0.2. Then 1.0 mmol of zirconium tetrachloride ZrCl4 and 0.5 mmol of tungsten disulfide WS2 were weighed and added to the above solution, stirred for 35 minutes to mix evenly, and then ultrasonically treated for 2.5 hours, transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated to 120°C for 22 hours; after heating, the autoclave was cooled to room temperature, the product was taken out and centrifuged at 8000 rpm for 10 minutes, and then washed with anhydrous ethanol and N, N-dimethylformamide for 3 times respectively, and dried in a vacuum drying oven at 75°C for 11 hours to obtain the catalyst WS2-UiO-66.

[0032] Example 2

[0033] 2.0 mmol of 2-aminoterephthalic acid was weighed and dissolved in 50 mL of a mixed solution of N, N-dimethylformamide and acetic acid in a volume ratio of 1:0.2. Then 1.0 mmol of zirconium tetrachloride (ZrCl4) and 1.0 mmol of tungsten disulfide WS2 were weighed and added to the above solution, stirred for 35 minutes to mix evenly, and then ultrasonically treated for 2.5 hours, transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated to 120°C for 22 hours; after heating, the autoclave was cooled to room temperature, the product was taken out and centrifuged at 8000 rpm in a centrifuge for 10 minutes, and then washed with anhydrous ethanol and N, N-dimethylformamide for 3 times respectively, and dried in a vacuum drying oven at 75°C for 11 hours to obtain the catalyst WS2-UiO-66.

[0034] Example 3

[0035] 2.0 mmol of 2-aminoterephthalic acid was weighed and dissolved in 50 mL of a mixed solution of N, N-dimethylformamide and acetic acid in a volume ratio of 1:0.2. Then 1.0 mmol of zirconium tetrachloride ZrCl4 and 1.5 mmol of tungsten disulfide WS2 were weighed and added to the above solution, stirred for 35 minutes to mix evenly, and then ultrasonically treated for 2.5 hours, transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated to 120°C for 22 hours; after heating, the autoclave was cooled to room temperature, the product was taken out and centrifuged at 8000 rpm in a centrifuge for 10 minutes, and then washed with anhydrous ethanol and N, N-dimethylformamide for 3 times respectively, and dried in a vacuum drying oven at 75°C for 11 hours to obtain the catalyst WS2-UiO-66.

[0036] Experimental Example 4 Photocatalytic degradation of phenol in water by catalyst

[0037] In this experimental example, common phenol is used as the target degradation product, and the degradation performance of the catalysts prepared in Examples 1-3 under visible light irradiation is tested; the specific steps are as follows: 0.05 g of the catalyst is weighed and dispersed into 150 mL of a phenol solution with a concentration of 40 mg / L, the mixed solution is stirred in the dark for 30 min to reach adsorption-desorption equilibrium, and then magnetically stirred for 75 min under an 800 w xenon lamp light source, 5 mL of sample is taken every 15 min and centrifuged, the upper layer liquid is aspirated and filtered with a filter membrane with a pore size of 0.22 μm, and the concentration of phenol in the solution at different treatment times is determined by ultraviolet-visible spectrophotometry.

[0038] The experimental results show that Figure 3 As shown, in the dark reaction stage of the first 30 minutes, Examples 1-3 all have simple physical adsorption, which leads to a decrease in the concentration of phenol. Compared with pure tungsten disulfide WS2, the porous characteristics of pure UiO-66 show a better adsorption effect; in the light reaction stage of 30-105 minutes, the degradation rate of phenol by WS2-UiO-66 catalyst can reach more than 90%, among which the degradation rates of Examples 1-3 are 91.2%, 98.6%, and 94.5%, respectively, and Example 2 shows excellent photocatalytic degradation effect.

[0039] In order to illustrate the improvement of catalyst performance, a control experiment was conducted and the results showed that Figure 1 As shown: under the same conditions, the degradation rates of pure tungsten disulfide WS2 and UiO-66 are only 30.4% and 23.7%; taking Example 2 as a reference, the removal rate of phenol by WS2-UiO-66 is increased by 65.2% and 74.9% compared with pure WS2 and UiO-66, respectively; indicating that the WS2-UiO-66 photocatalyst has excellent catalytic degradation performance for phenol under light.

[0040] Experimental Example 5 Effect of Catalyst Amount on Photocatalytic Degradation of Phenol

[0041] In order to explore the effect of catalyst dosage on the degradation effect, Example 2 with excellent catalytic effect was selected as the research object; the specific steps are as follows: 0.01g, 0.02g, 0.03g, 0.04g, 0.05g, 0.10g, 0.15g, and 0.20g of the catalyst prepared in Example 2 were weighed respectively, and then dispersed in 8 groups of the same 150mL phenol solution with a concentration of 40mg / L, respectively, and the mixed solution was stirred in the dark for 30min to reach adsorption-desorption equilibrium, and after magnetic stirring for 60min under an 800w xenon lamp light source, 5mL of the sample was centrifuged, the upper layer liquid was aspirated and filtered with a filter membrane with a pore size of 0.22μm, and the concentration of phenol in the solution was determined by UV-visible spectrophotometry; the experimental results are as follows Figure 2 As shown, when the usage amount is 0.01g-0.05g, it shows a degradation effect of more than 90%, among which the highest degradation rate is 95% at a usage amount of 0.03g; this phenomenon shows that within a certain range, as the amount of catalyst increases, the catalytic activity also increases, because more catalysts provide more active sites, which can capture more photons and reactant molecules to maximize the reaction rate; however, excessive photocatalysts may cause light scattering and light shielding effects, reducing the utilization rate of light; for example, when the catalyst dosage is 0.10g and 0.20g, the degradation rate drops to 80% and 60%; therefore, under the conditions of light source intensity and reactant concentration, a small amount of the composite catalyst (less than 0.05g) shows excellent degradation efficiency.

[0042] In the present invention, a catalyst with high catalytic activity is prepared in situ by a solvothermal method. Due to the in situ synthesis, a close combination of WS2-UiO-66 is formed, the contact interface is increased, and the catalyst has excellent structural stability and multiple cycle performance; the cycle test results are as follows Figure 3 As shown, after 4 consecutive photocatalytic degradation experiments in Example 2, the degradation rate of phenol by the WS2-UiO-66 catalyst did not decrease significantly. After four cycles of experiments, the degradation rate could still reach 92.4%, which was only 6.4% lower than that after the first photocatalytic degradation.

[0043] The above test results show that the WS2-UiO-66 catalyst is a catalytic material prepared by a one-step solvent thermal reaction of tungsten disulfide WS2, 2-aminoterephthalic acid and zirconium salt; the three-dimensional structure of UiO-66 formed by the composite effectively disperses tungsten disulfide WS2 evenly in the system, while improving the adsorption capacity and specific surface area of ​​the catalyst, it also promotes the separation of photogenerated electron-hole pairs, and the amino groups on the organic ligands increase the activated contact sites of the reaction, thereby improving the photocatalytic efficiency; in the photocatalytic degradation of phenol, the degradation effect is significantly improved compared to the single WS2 photocatalytic degradation; in addition, only a small amount of catalyst (less than 0.05g) is required in the catalytic reaction to achieve a degradation efficiency of more than 90% after 60 minutes of photoreaction.

[0044] Phenol is widely used in industry as a disinfectant, preservative, flame retardant, and dye. However, phenol is potentially harmful to the environment and human health. Phenol is not easily degraded in the environment and can exist in soil and water for a long time. It is difficult to completely remove it in conventional sewage treatment systems, and it can accumulate in organisms through the food chain, affecting the health of organisms. In addition, because it is difficult to degrade in the environment, it also poses a serious threat to the ecosystem.

[0045] The research and application of photocatalytic degradation of phenol is of great significance for environmental protection and industrial wastewater treatment. Through photocatalytic technology, phenol can be efficiently degraded to reduce its harm to the environment; in addition, photocatalytic technology can also be applied to the degradation of other organic pollutants, providing a sustainable technical approach for water treatment and environmental purification.

Claims

1. A method for preparing a catalyst with high catalytic activity, characterized in that: Zirconium salt and tungsten disulfide are added to a mixed solution of N,N-dimethylformamide and acetic acid as organic ligands, stirred and mixed evenly, and then transferred to a stainless steel autoclave lined with polytetrafluoroethylene for heating and reaction after ultrasonic dissolution; after the heating is completed, the autoclave is cooled to room temperature, the product is taken out and centrifuged, and washed with anhydrous ethanol and DMF for 3 times each, and then dried in a vacuum drying oven to obtain the catalyst WS2-UiO-66.

2. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The zirconium salt is any one of zirconium tetrachloride and zirconium nitrate.

3. A catalyst with high catalytic activity and a preparation method thereof according to claim 1, characterized in that: The preparation steps of the tungsten disulfide are as follows: S1: Mix 20 mmol of sodium tungstate and 20 mmol of sodium sulfide in 50 mL of distilled water and stir for 30 min to form a transparent solution; S2: The transparent solution prepared in S1 was introduced into a stainless steel autoclave lined with polytetrafluoroethylene and heated at 220 °C for 6 h; S3: After the autoclave is cooled naturally to room temperature, centrifuge, remove the supernatant, and wash with ethanol and deionized water several times; S4: Dry in a vacuum drying oven at 70°C for 12 h to obtain tungsten disulfide powder.

4. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The organic ligand is 2-aminoterephthalic acid.

5. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The molar ratio of the zirconium salt, tungsten disulfide and organic ligand is 1:0.5-1.5:

2.

6. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The volume ratio of the N,N-dimethylformamide to acetic acid is 1:0.

2.

7. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The stirring and mixing time is 30-40 minutes; the ultrasonic treatment time is 2-3 hours.

8. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The heating temperature of the autoclave is 110-130° C., and the heating time is 24 hours.

9. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The centrifugal speed is 8000 rpm and the time is 10 min.

10. The method for preparing a catalyst with high catalytic activity according to claim 1, characterized in that: The drying temperature in the vacuum drying oven is 70-80° C., and the drying time is 10-12 hours.